Identification of Bacteria in Yellowfin Tuna (Thunnus albacares) With the Addition of Salt - Lewar, Yulius Frederik; Nawastuti, Dati; Batafor, Yosephina M.J. (Civiliza Publishing, Indonesia., 2025)
One of the processed fishery products is se'i fish. Se'i is smoked meat processed traditionally using a smoking method with firewood and kosambi leaves. This study aims to identify the presence of Salmonella sp. and Escherichia coli bacteria in se'i tuna (Thunnus albacares) with salt treatment, as well as to evaluate factors that influence product safety. Tuna se'i samples were treated with coarse and fine salt additions with variations of 5 g and 10 g, as well as a control without salt. Bacterial identification was carried out using standard microbiological methods. The results showed that all samples, both control and salt treatment, were negative for Salmonella sp. and E. coli. This indicates that salt variation did not affect the results because all samples did not contain these bacteria. The dominant influencing factor was the use of garlic as a seasoning that contains allicin compounds with antibacterial properties that can inhibit the growth of spoilage bacteria. In addition, the packaging aspect plays an important role in improving the safety, quality, and competitiveness of se'i tuna products because it is safe for consumption and has great potential as a traditional specialty product.